Exploring Character Education Values on Picture Dialogue in English Textbooks for Eight Grade of Junior High School - Hamidah, Nindi Maulia; Yanto, Elih Sutisna; Ahmad, Yousef Bani (STKIP Yapis Dompu, 2022)
The purpose of this study was to determine the values of character education contained in the textbook When English Rings A Bell Curriculum and Book Center for SMP/MTs Class VIII, Ministry of Education and Culture of the Republic of Indonesia revised edition 2017. This research is qualitative using content analysis. The data used in this study are in the form of texts in textbooks. The main instrument of the study was researcher and the data sheet was also used as the second instrument. Several steps were taken during data collection: (1) reading carefully; (2) understanding certain parts related to the focus of intensive research; (3) marking certain parts related to the research focus; and (4) making data descriptions accompanied by process of coding and inserting data into tables. In analyzing the data, this study uses critical discourse analysis technique. The subjects are 6 chapters in the textbook When English Rings A Bell Curriculum and Book Center for SMP/MTs Class VIII, Ministry of Education and Culture of the Republic of Indonesia revised edition 201. The objects are 18 characters values described by the Ministry of National Education. The findings of character education values in the textbook When English Rings A Bell Curriculum and Book Center for SMP/MTs Class VIII, Ministry of Education and Culture of the Republic of Indonesia revised edition 2017 as many as 10 characters values, namely (1) discipline; (2) interest reading; (3) curiosity; (4) responsibility; (5) creative; (6) communicative/friendliness; (7) appreciative; (8) social care; (9) environmental awareness; and (10) tolerance.